Business Plan Development Guide - Swanson, Lee (Open textbook library., 2017)
This textbook and its accompanying spreadsheet templates were designed with and for students wanting a practical and easy-to-follow guide for developing a business plan. It follows a unique format that both explains what to do and demonstrates how to do it.